2009
DOI: 10.1155/2009/153597
|View full text |Cite
|
Sign up to set email alerts
|

Blau Syndrome-Related CARD15/NOD2 Mutations Are Not Linked to Idiopathic Uveitis in Spanish Patients

Abstract: Abstract. Uveitis is a clinical feature of the Blau syndrome, a disease linked to CARD15 (also referred to as NOD2) mutations. Three main mutations in this gene (R334W, R334Q and L469F) have been reported as Blau syndrome risk factors, a disease that manifests uveitis as one of its clinical features. However, little is known on the involvement of this gene in idiopathic uveitis. We thus sought to determine the frequency of these Blau-related CARD15 mutations in a cohort of Spanish patients with idiopathic uvei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…In contrast to previous reports [ 11 , 12 ], our study, showed a statistical association between the variant P268S/SNP5 (SNP rs2066842) and ACU, both idiopathic and associated with other rheumatic disease. In our cohort the incidence of variations was not significantly different between our patients with idiopathic chronic uveitis and those with chronic uveitis associated to auto-immune diseases.…”
Section: Implications Of the Hypothesiscontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous reports [ 11 , 12 ], our study, showed a statistical association between the variant P268S/SNP5 (SNP rs2066842) and ACU, both idiopathic and associated with other rheumatic disease. In our cohort the incidence of variations was not significantly different between our patients with idiopathic chronic uveitis and those with chronic uveitis associated to auto-immune diseases.…”
Section: Implications Of the Hypothesiscontrasting
confidence: 99%
“…The role of NOD2/CARD15 gene as a key regulator of innate immunity in the eye has been elucidated by studies performed on murine models,which are knockout for NOD2/CARD15, which showed an increased susceptibility to uveitis [ 9 , 10 ]. However the first reports conducted on patients affected by idiopathic uveitis has failed to demonstrate a role for this gene in this disease; two studies conducted on a large cohort of spanish patients with idiopathic uveitis suggested that NOD2/CARD15 variants do not seem to predispose to thee disease [ 11 , 12 ]. In order to investigate the possible role of this gene in ACU, we have studied NOD2/CARD15 variants and the genotype-phenotype correlation in a cohort of patients with idiopathic uveitis and uveitis associated with other inflammatory diseases.…”
Section: Presentation Of the Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…So far, more than 10 mutations in CARD15 which are closely associated with the disease have been reported in different races and regions. R334Q and L469F were the earliest discovered mutations (Miceli-Richard et al, 2001), and R334W and R334Q were the most frequently found mutations, which were observed in more than 50% of patients (Milhavet et al, 2008;Rodriguez-Perez et al, 2009) (Milman et al, 2009). Further studies of the sporadic cases of Blau syndrome revealed more mutations, such as D382E, E383G, G464W, G481D, W490L, C495Y, H496L, M513T, R587C, T605P, A612T, and N670K.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that the polymorphisms in the NOD2 gene are associated with the occurrence of some infectious diseases and granulomatous inflammation, including mycobacterium tuberculosis 13 , Crohn’s disease 14 , and Blau’s syndrome 1517 .…”
Section: Introductionmentioning
confidence: 99%